Immobilization of heavy metals for building materials in the construction industry - An overview - Kamal N.L.M.; Beddu S.; Syamsir A.; Mohammad D.; Itam Z.; Hamid Z.A.A.; Manan T.S.A. (Elsevier Ltd, 2023)
Ash handling; Ashes; Cement industry; Coal ash; Coal combustion; Coal fired power plant; Coal industry; Construction industry; Fossil fuel power plants; Heavy metals; Silicates; Thermoelectric power plants; Waste incineration; Alternative materials; Bottom ash; Buildings materials; Classifieds; Coal bottom ash; Coal combustion byproducts; Coal-fired power plant; Hazardous wastes; Heavy metal immobilization; Immobilisation; Coal